Wybór strategiczny jako wyzwanie współczesnego zarządzania - Kaleta, Andrzej (Strategic Choice as a Challenge of Contemporary Management, 2006)
The article indicates the necessity for strategic choice of specialization in the context of growing demands of competition. Specialization becomes a dominating trend despite high unpredictability which impedes the choice. Efficient strategic choice requires acquiring a long-term perspective and combining it with the most valuable competences, constant verification of decisions and development within the chosen specialization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 318-328